Gastrointestinal neuroendocrine tumors: Searching the optimal treatment strategy—A literature review. (February 2016) - Berardi, Rossana; Rinaldi, Silvia; Torniai, Mariangela; Morgese, Francesca; Partelli, Stefano; Caramanti, Miriam; Onofri, Azzurra; Polenta, Vanessa; Pagliaretta, Silvia; Falconi, Massimo; Cascinu, Stefano
Highlights: Neuroendocrine tumors of the gastro-entero-pancreatic system (GEP-NETs) are a heterogeneous group of neoplasms, with different behavior. A shared therapeutic sequence for GEP-NET treatment still does not exist. The aim of this review is to identify the first and further better approaches among all available therapeutic options. Abstract: Neuroendocrine tumors of the gastro-entero-pancreatic system (GEP-NETs) are a heterogeneous group of neoplasms, with different malignant potential and behavior. Many treatment options are available. Surgery should be considered for localized tumors and in some selected cases of metastatic disease. Somatostatin analogs, useful for symptoms control in functioning tumors, are also effective to inhibit tumor progression in specific settings. The multi-TKI sunitinib and of the mTOR-inhibitor everolimus are efficacy for metastatic pancreatic NET (P-NET) treatment. Chemotherapy is generally used in symptomatic and progressive NETs. Peptide receptor radionuclide therapy (PRRT) should be recommended after failure of medical therapy. For tumors confined to the liver ablative techniques should be considered. Nevertheless a shared therapeutic sequence for GEP-NET treatment still does not exist. In this review, we analyzed available data trying to identify the better treatment strategy and to suggest potential therapeutic algorithms distinguishing P-NETs from gastrointestinal NETs (GI-NETs).